Change of transfusion and treatment paradigm in major trauma patients. (23rd May 2017) - Stein, P.; Kaserer, A.; Sprengel, K.; Wanner, G. A.; Seifert, B.; Theusinger, O. M.; Spahn, D. R.
Summary: Trauma promotes trauma‐induced coagulopathy, which requires urgent treatment with fixed‐ratio transfusions of red blood cells, fresh frozen plasma and platelet concentrates, or goal‐directed administration of coagulation factors based on viscoelastic testing. This retrospective observational study compared two time periods before (2005–2007) and after (2012–2014) the implementation of changes in trauma management protocols which included: use of goal‐directed coagulation management; admission of patients to designated trauma centres; whole‐body computed tomography scanning on admission; damage control surgery; permissive hypotension; restrictive fluid resuscitation; and administration of tranexamic acid. The incidence of massive transfusion (≥ 10 units of red blood cells from emergency department arrival until intensive care unit admission) was compared with the predicted incidence according to the trauma associated severe haemorrhage score. All adult (≥ 16 years) trauma patients primarily admitted to the University Hospital Zürich with an injury severity score ≥ 16 were included. In 2005–2007, the observed and trauma associated severe haemorrhage score that predicted the incidence of massive transfusion were identical, whereas in 2012–2014 the observed incidence was less than half that predicted (3.7% vs. 7.5%). Compared to 2005–2007, the proportion of patients transfused with red blood cells and fresh frozen plasma was significantly lower in 2012–2014 in both the emergency department (43% vs. 17%; 31% vs. 6%, respectively), and after 24 h (53% vs. 27%; 37% vs. 16%, respectively). The use of tranexamic acid and coagulation factor XIII also increased significantly in the 2012–2014 time period. Implementation of a revised trauma management strategy, which included goal‐directed coagulation management, was associated with a reduced incidence of massive transfusion and a reduction in the transfusion of red blood cells and fresh frozen plasma. Abstract : ☛ CPD available athttp://www.learnataagbi.org/